2020
DOI: 10.3389/fmed.2020.00299
|View full text |Cite
|
Sign up to set email alerts
|

High APRIL Levels Are Associated With Slow Disease Progression and Low Immune Activation in Chronic HIV-1-Infected Patients

Abstract: Objective: B-cell-activating factor (BAFF) has been determined to be involved in HIV-1 infection and is correlated with disease progression, while its homologous molecule, a proliferation-inducing ligand (APRIL), is less frequently reported, and its role remains unclear. We aimed to characterize the APRIL levels in subjects with different HIV-1 infection statuses and determine the relationships with disease progression and immune activation. Methods: The plasma levels of APRIL were compared among 17 long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Interestingly, TNFSF13, the gene encoding A proliferation-inducing ligand (APRIL), was found to be of the most protective genes in the NHP trials [28], and we found the expression levels of this gene to be increased in monocytes from HESNs when compared to the other groups. Of interest, APRIL has been associated with slower HIV disease progression in LTNP [50]. Therefore, our data suggest that natural immunity to HIV in HESNs shares some highly protective features elicited by vaccine regimens known to confer some level of protection in humans and NHP.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, TNFSF13, the gene encoding A proliferation-inducing ligand (APRIL), was found to be of the most protective genes in the NHP trials [28], and we found the expression levels of this gene to be increased in monocytes from HESNs when compared to the other groups. Of interest, APRIL has been associated with slower HIV disease progression in LTNP [50]. Therefore, our data suggest that natural immunity to HIV in HESNs shares some highly protective features elicited by vaccine regimens known to confer some level of protection in humans and NHP.…”
Section: Discussionmentioning
confidence: 65%
“…The fact that high levels of BAFF seem to correlate with low HDL and high LDL could be related to the fact that these modulations are all related to the HIV context, and thus could reflect HIV disease progression. This could also explain the positive correlation of APEIL with HDL levels and negative correlation with the LDL/HDL ratio, as APRIL has also been found to be related to a slower HIV disease progression and a lower immune activation [ 52 ]. It is important to note that the CHACS does not control for statin usage.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that high levels of BAFF seem to correlate with low HDL and high LDL could be related to the fact that these modulations are all related to the HIV context, and thus could reflect HIV disease progression. This could also explain APRIL’s positive correlation with HDL levels and negative correlation with the LDL/HDL ratio, as APRIL has also been found to be related to a slower HIV disease progression and a lower immune activation [50]. It is important to note that the CHACS does not control for statin usage.…”
Section: Discussionmentioning
confidence: 99%